Fatigue study on 3D cracks initiated at corrosion zone in offshore pipelines - Tan, Boon Hian (Nanyang Technological University, 2023)
Pipelines, which often consists of long circular structures welded together, are major oil and gas industry tools used in exploration, drilling, production, and that installing and operating these structures in deep waters places unique demands on them. The technical challenges of these field since then have spawned significant research and development efforts in a broad range of area. One of the many areas of research include the investigation on the effect of corrosion under fatigue conditions. [1] Corrosion is often one of the main reasons for structural degradation in offshore structures. It affects the life of pipelines and often leads to catastrophic failure, leakage, loss of product, pollution to the environment, and in some cases loss of life. In all the various forms of corrosion, pitting corrosion is identified as the most hazardous of them all. Pitting corrosion is a localised accelerated dissolution of metal that occurs as a numerous real-life factor such as temperature, variable loads, vibration, and microbial activities reduces the effectiveness of the various protective layers on the metal surface. [2] The current study presents the investigation on the fatigue behaviour using the theory of finite element method to simulate the fatigue behaviour of various scenario of 3 dimensional semi-elliptical cracks under a cyclic tensile force by using ANSYS Workbench 19.2. The focus is to investigate the influence of corrosion on the cracks that are present within the steel structures.